Healthcare workers' industrial action in Nigeria: a cross-sectional survey of Nigerian physicians - Obinna Ositadimma Oleribe; Deborah Udofia; Olabisi Oladipo; Temitope Arike Ishola; Simon D. Taylor-Robinson (BMC, 2018)
Abstract Background The Nigerian health system has been plagued with numerous healthcare worker strikes (industrial action) at all levels. The purpose of this study is to document physicians' views on healthcare worker-initiated strike action in Nigeria and represent a follow-on to a previous study where poor leadership and management were cited as the most common cause of strike action by healthcare workers. Methods A cross-sectional, descriptive study was executed between April and June 2017. We used a self-administered pre-tested structured questionnaire with open-ended questions to allow for better expression of participants' views. Participants were drawn mainly from the recently concluded West African College of Physicians (WACP)/Royal College of Physicians (RCP) Millennium Development Goal 6 Partnership for African Clinical Training (M-PACT) course. They represented the six geopolitical zones of Nigeria. Data were analysed using SPSS v 23. Simple frequencies were performed, and relevant tables/charts were developed. Results A total of 58 physicians (out of 131 participants reached) responded to the study, giving a response rate of 44.3%. 62.1% were males, 67.9% were between the ages of 30 and 39 years, and over 60% of respondents graduated prior to 2010. Poor staff welfare was cited by 16.7% as the commonest cause of strikes in the healthcare system. Other causes cited were salary issues (13.9%), leadership and management (13.9%), poor hospital infrastructure (11.1%), poor guidelines and services (11.1% each) and inter-professional disputes (5.6%). The negative consequences of strikes, the groups who benefit from them and solutions to the strikes were enumerated, including training physicians in leadership skills by 98.2% of respondents. Conclusion Poor staff welfare, salary and leadership/management and governmental inability to implement agreements were the common causes of healthcare worker strikes in this study. These strikes resulted in disruption to service delivery and training programmes, increased morbidity and mortality of patients and loss of confidence in the hospitals and the healthcare professions. The participants recommended that the Federal Government respects agreements made with the management of healthcare institutions, implements the National Health Act and ensures that only leaders and managers who are formally trained are appointed to healthcare management positions.